An Approach to Assist the Design of User-Centered Solutions based on Generative AI - Queiroz, Thiago; Macedo, Gretchen T. de; Steinmacher, Igor; Conte, Tayana; Oran, Ana Carolina; Gadelha, Bruno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
User-Centered Design (UCD) aims to ensure software quality by aligning its development with user needs, enabling users to guide project decisions and contribute to the overall quality of the product. Some methodologies, such as Design Thinking and Lean UX, incorporate UCD, but they often lack a rigorous structure that focuses on the rapid validation of solutions. This paper investigates the Design Sprint, a UCD approach, which offers short development cycles for validating solutions with the users. We developed an approach based on generative Artificial Intelligence (AI) to automate Design Sprint activities through structured prompts designed with prompt engineering techniques. We evaluated the proposed approach through a feasibility study involving 38 participants. The study included introductory training and the practical application of the prompts in team-defined projects. Results indicate a predominantly positive reception of the proposed approach, with 85,7% of the teams rating all artifact-generating activities as either “very helpful” or “helpful” during the Design Sprint phases of understanding, sketching, decision-making, and prototyping, which reinforces the feasibility of the approach presented in this study.